Malnutrition in Children Aged 6-59 Months in Mugu District - Sharma, K R (Journal of Nepal Health Research Council, 2012)
Background: Malnutrition is one of the leading causes of child morbidity and mortality. The severity of hunger in mountain and hill districts of Mid- and Far-Western Development Regions is a serious concern. Mugu, is one of the most remote and least developed districts of Nepal, periodically facing food insufficiency. This study was carried out to evaluate the malnutrition status of the most vulnerable group of children (6-59 months age group) in Mugu district. Methods: This study conducted in Mugu district was prospective and observational. Nutritional status of children aged 6-59 months were assessed by measuring mid-upper arm circumference by using MUAC tape and data was collected by interviewing caretakers. The data were analyzed and compared to the national figure. Results: Altogether 198 children aged 6-59 months were recruited for this study. Among them 49% were boys and 51% were girls. According to MUAC criteria, 1% of children had suffered from Severe Acute Malnutrition (SAM), 17% had Moderate Acute Malnutrition (MAM) and 82% had adequate nutritional status. Conclusions: The prevalence of Acute Malnutrition is high in Mugu district. The important factors, among numerous others are food scarcity, poor hygiene and environmental practices, lack of care of the mother towards her child due to priority given to work and lack of knowledge about proper child feeding/care. Â Keywords: Malnutrition; Mid Upper Arm Circumference (MUAC); Moderate Acute Malnutrition (MAM); Severe Acute Malnutrition (SAM).